Os equinóides albianos (cretáceo inferior) do Brasil e seu possível valor estratigráfico - Brito, Ignacio Machado (Anuário do Instituto de Geociências, 1991)
The occurrence of Albian Echinoids in Brazil has been reported in the Santana Formation (Araripe basin), the Riachuelo Formation (Sergipe basin) and the Algodões Formation (Camamu basin). In this paper we discuss the possibility of a wide distribution of the brazilian species in other continents such as North America and West Africa.